PENGAWETAN KAYU TISUK (Hibiscus macrophyllus Roxb.) DAN SUKUN (Artocarpus horridus Jarret.) SECARA SEL PENUH DENGAN BAHAN PENGAWET CCB DAN BORON - Sasa Abdurrohim; Jajang Nurjaman; Anne Hadiane (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Tisuk (Hibiscus macrophyllus Roxb.) and sukun (Artocarpus horridus Jarret.) trees are numerously planted by the rural community in Ciamis regency. The wood portion of tisuk has been much in use for constructions material and furniture, while sukun is intended as multipurpose plants. Due to poor or low durability of the wood portion in both species, prior to its uses, it should be preserved or treated. Preservation scheme for both wood species with particular preservatives, unfortunately, has not yet been available. Therefore. a through investigation is urgently required to work out such a proper scheme.Inherent with such, ninety pieces or wood samples, measuring of 5 by 5 by 30 cm, were prepared from each of both species for the treating trial. After being dried, the samples pieces were treated with CCB (copper-chrome-boron) and boron preservatives by the full-cell process. The preservatives (CCB and boron) were each used in solution at three varying concentrations, i.e. 2, 3, and 4 percent. Initial and final vacuums were maintained at 600 mmHg for 30 and 15 minutes respectively. On the other hand, the treating phase was employed at three variable pressures i.e. 4, 6, and 8 hours, for one hour.The results revealed that both tisuk and sukun were satisfactorily treatable with CCB solution at 4 and 2 percent concentrations, respectively. For both CCB treated wood species used under roof and exposed to the open air without ground contact the recommended pressures were 4 and 8 atmospheres. A schedule treatment 4 and 2 percent boron with 4 atmospheres pressure is respectively recommended for tisuk and sukun used under roof without ground contact.